Phase stabilization of cesium lead iodide perovskites for use in efficient optoelectronic devices - Handong Jin; Yu-Jia Zeng; Julian A. Steele; Maarten B. J. Roeffaers; Johan Hofkens; Elke Debroye (NPG Asia Materials)
Abstract All-inorganic lead halide perovskites (LHPs) and their use in optoelectronic devices have been widely explored because they are more thermally stable than their hybrid organic‒inorganic counterparts. However, the active perovskite phases of some inorganic LHPs are metastable at room temperature due to the critical structural tolerance factor. For example, black phase CsPbI3 is easily transformed back to the nonperovskite yellow phase at ambient temperature. Much attention has been paid to improving the phase stabilities of inorganic LHPs, especially those with high solar cell efficiencies. Herein, we discussed the origin of phase stability for CsPbI3 and the strategies used to stabilize the cubic (α) phase. We also assessed the CsPbI3 black β/γ phases that are relatively stable at nearly room temperature. Furthermore, we determined the relationship between phase stabilization and defect passivation and reviewed the growing trend in solar cell efficiency based on black phase CsPbI3. Finally, we provide perspectives for future research related to the quest for optimum device efficiency and green energy.